The History of Buddhist Thought - Thomas, Edward J. (Brill | Manohar Publishers & Distributors, 2024)
Buddhism and its history are the most revolutionary things which happened in the world history. Buddha and his teaching proved to be an inspiration for many, including Dr. B.R. Ambedkar. The History of Buddhist Thought covers literatures on the Buddhist philosophy. The book talks about the Early Sangha literature, which comprises the Early Buddhist corpus available on Buddha. The relationship between the Buddhism and Brahmanism is an interesting aspect, even though Buddhism was presented as a critic of the Hindu religion. However, the important themes that are touched in this volume is the concept of Buddhahood, Bodhisattva, concept of voidness and consciousness, and the stage of nirvana, which is another important aspect in Buddhist religion. And finally, it covers the interaction between Buddhism and modern thought.